Clockwork destiny - Anderson, Kevin J., 1962-; Peart, Neil (Anderson, Kevin J., 1962- Clockwork, 2022)
"The final volume in the New York Times-bestselling, award-winning steampunk trilogy by Kevin J. Anderson and legendary Rush drummer Neil Peart. In Kevin J. Clockwork Angels and Clockwork Lives, readers met the optimistic young hero Owen Hardy, as well as the more reluctant adventurer Marinda Peake, in an amazing world of airships and alchemy, fantastic carnivals and lost cities. Now Owen Hardy, retired and content in his quiet, perfect life with the beautiful Francesca, is pulled into one last adventure with his eager grandson Alain. This final mission for the Watchmaker will take them up to the frozen lands of Ultima Thule and the ends of the Earth. Marinda Peake must undertake a mission of her own, not only to compile the true life story of the mysterious Watchmaker, but also to stop a deadly new group of anarchists. The Clockwork trilogy is based on the story and lyrics from the last album of musical titans Rush, with Anderson and Peart expanding the world, stories, and characters. The two developed the final novel in the trilogy in the last years of Peart's life, and more than a year after his passing, Anderson returned to that unfinished project, with the full support of Peart's wife, bringing Owen and Marinda's stories to a satisfying and stirring conclusion"--